Effect of Mass Formation on Indoor Thermal Performance in the Arab Region - osama abo einan; Merhan Shahda; Rash Adil (Port Said Engineering Research Journal, 2019)
The global energy demand has increased, which led to a severe shortage of energy sources in the world. Buildings consume alone about 40% of total energy production. This is mainly due to the lack of consideration of climatic and environmental factors in the early steps of building design. So we have many buildings with low thermal performance.In an attempt to find ways to increase the thermal performance of the building, this paper focuses on the study of the relationship between the thermal performance of the building and the most important element in the design of the building is the building shape. The paper focused on the Arab world's climate, especially in hot climates (hot-dry, hot-humid).The simulation was conducted using Design Builder program in two cities, in Jeddah in Saudi Arabia (which represents a hot-dry climate) and the other city is Port Said in Egypt (which represents a hot-humid climate). Several shapes were compared and these shapes are circle, square, rectangle by different ratios, L shape, U shape and courtyard. The results varied in each climate:In hot- dry climate: 1) The courtyard shape helped in saving 53% of the energy. 2) By directing the building to the north or south, saves 10% of the energy. 3) When the percentage of openings 10% provided 44% of the energy.In hot-humid climate: 1) The square shape has the best thermal performance since it saves about 46.5% of the energy. 2) The building which directed to the north provides about 14% of the energy. 3) The percentage of openings in the building when 10% provides 52.8% of energy.